Conjoined ischiopagus twins - Olcay, Işık; Yücesan, Selçuk; Zorludemir, Ünal (The Turkish Journal of Pediatrics, 1985)
A case of conjoined ischiopagus twins is described. This is the first case surgically separated in Turkey. Although it is advisable to delay the operation to allow time for diagnostic testing to determine the degree of fusion and the extent of malformations present, we had to operate without delay in view of the negative effects of the one on the other.
Keywords: conjoined twins; ischiopagus twins